A discontinuous Galerkin method for simulating the effects of arbitrary discrete fractures on elastic wave propagation. Issue 2 (26th May 2017) - Zhan, Qiwei; Sun, Qingtao; Ren, Qiang; Fang, Yuan; Wang, Hua; Liu, Qing Huo
Abstract: We develop a non-conformal mesh discontinuous Galerkin (DG) pseudospectral time domain (PSTD) method for 3-D elastic wave scattering problems with arbitrary fracture inclusions. In contrast to directly meshing the exact thin-layer fracture, we use the linear-slip model, one kind of transmission boundary condition, for the DG scheme. Intrinsically, we can efficiently impose a jump-boundary condition by defining a new numerical flux for the surface integration in the DG framework. This transmission boundary condition in the DG-PSTD method significantly reduces the computational cost. 3-D DG simulations and accurate waveform comparisons validate our results for arbitrary discrete fractures. Numerical results indicate that fractures have a significant influence on wave propagation.